Assessing the strength of evidence for records of Night Parrots at Kalamurina Wildlife Sanctuary (South Australia) and Diamantina National Park (Queensland), 2016–2018. (2nd April 2020) - Menkhorst, Peter; Fitzsimons, James; Loyn, Richard; Woinarski, John
ABSTRACT: The Night Parrot Pezoporus occidentalis is one of the least known and most threatened of Australia's bird species. In recent decades, breeding has been confirmed at only two remote regions in inland Australia. Consequently, reports of its presence in new locations have important conservation implications and elicit intense public interest. Between 2016 and 2018, following targeted searches, the Australian Wildlife Conservancy (AWC) reported the presence of Night Parrots on their Kalamurina Wildlife Reserve (South Australia) and the Diamantina National Park (Queensland). In response to questions raised from within the Australian ornithological community, AWC appointed an independent panel to assess the adequacy of the evidence for the presence of Night Parrots at these two locations. The panel was tasked with considering three lines of evidence: a single feather discovered at Kalamurina in 2017, calls recorded on an acoustic recorder at Kalamurina in 2018 and photographs of three nests with eggs taken at Diamantina National Park in 2016. The panel concluded that each of the three lines of evidence was insufficient to demonstrate conclusively the occurrence of Night Parrots at either Diamantina National Park or Kalamurina Wildlife Reserve. Here we present a summary of the panel's findings, to maintain these findings permanently on the public record.